Upcycling of Cupric Chloride Waste Solution from PCB Manufacturing for Antibacterial Copper Nanoparticles - Tapany Patcharawit; Chatisa Kansomket; Napat Mahiwan; Sumita Chailoi; Thanapon Chandakhiaw; Tanongsak Yingnakorn; Teerawut Tunnukij; Sakhob Khumkoa (Recycling, 2025)
Issues encompassing hazardous waste management face challenges, particularly those involving the manufacture of electronic devices such as PCBs that are in high demand with continual growth. Therefore, upcycling to create new products viable for highly valued markets emphasizes alternative solutions towards the circular economy. This research highlights the advantages of copper sulfate recovery from the cupric chloride etching waste solution from PCB manufacturing, combined with the synthesis of copper nanoparticles for antibacterial application. First, aluminium cementation, sulfuric acid leaching, and crystallization were incorporated in the recovery step to ensure a high purity of 99.95% and a recovery of 94.76%. Aluminium cementation selectively offered copper-containing precipitates suitable for leaching to gain high-purity recovered products. In the second step, copper nanoparticles were synthesized using 0.01–0.20 M copper sulfate precursors via sonochemical reduction. In total, 1–5 mL of hydrazine and 5–30 mL of 0.01 M ethylene glycol were added into a 50 mL precursor as reducing and capping agents, respectively. Hydrazine addition under high pH played a key role in controlling the shape, size, and purity of the copper nanoparticles, required for their antibacterial properties. The optimum condition gave spherical or polygonal copper nanoparticles of 54.54 nm at 99.95% purity and >92% recovery. The antibacterial test of the synthesized copper nanoparticles using E. coli via agar well diffusion exhibited a zone of inhibition (ZOI) of 50 mm at 127 mg/mL, similar to the antibiotic-controlled condition, proving their antibacterial potential. Along with process effectiveness, a feasibility study of the inventing process confirmed the environmental and economic impacts of minimizing energy consumption and processing time, which are competitive with respect to the existing recycling technologies.